Indian Project Managers' Experience with the effect of PMI Ethical Principles on Software Project Performance: Examining the Impact of PMI Ethical Principles on Software Project Success for Indian Project Managers (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Since the Indian IT and ITES businesses have grown so rapidly, global software projects mustbe completed successfully. These attempts have not revealed the key to continuously successfulsoftware projects. Therefore, software professionals must consider project management as a whole asappraising software projects just on technical merits may not be adequate in today's changing globalmarketplaces. Software project success must be examined from several aspects, with a focus onintangibles. In light of this and the increased focus in PM literature on project managers' ethical conductwith concerned stakeholders, our research examines how Indian project managers' ethical behaviouraffects software development project success. Even though the PMI clearly describes these four basicethical requirements and their connected aspirational and necessary behaviour, it is largely a Westerncultural concept of project ethics. Project managers sometimes face ethical difficulties while managingbig, worldwide projects, yet the PMI doesn't provide any advice. Therefore, project managers from avariety of cultural backgrounds must have a deep awareness of these widely accepted standards for anystudy on ethics and project performance to be valid. This material will aid PMI and project managers byhelping them understand the possible challenges of applying these principles to real-world projects.